Crystal properties of atomic-layer deposited beryllium oxide on crystal and amorphous substrates - Lee, Seung Min; Jang, Yoonseo; Yum, Jung Hwan; Larsen, Eric S.; Lee, Woo Chul; Kim, Seong Keun; Bielawski, Christopher W.; Oh, Jungwoo (IOP PUBLISHING LTD, 2019)
We present the crystal properties of beryllium oxide (BeO) films on Si (100), GaN (001), and amorphous SiO2 substrates grown by atomic-layer deposition (ALD). Because of the strong bonding interactions intrinsic to beryllium, BeO thin films have been grown in crystalline phases regardless of the substrate type. Transmission electron microscopy revealed crystallized BeO films with small interfacial layers. The epitaxial relationships and domain-matching configurations were confirmed by crystal simulation. Using x-ray diffraction analyses, ALD BeO films with thicknesses of 50 nm showed wurtzite (002) crystal phases for all substrates studied. Raman spectroscopy confirmed that the crystallinity of the BeO film grown on GaN was superior to that on Si and SiO2 substrates. Atomic force microscopy and water contact angle goniometry measurements indicated that the BeO film grown on GaN in a planar mode was due to its low film energy.
Keywords: DOMAIN EPITAXY; BEHAVIOR; GROWTH; FILMS; GAN